ISOLASI NANOSELULOSA DARI TANDAN KOSONG SAWIT MENGGUNAKAN HIDROLISIS ASAM SEBAGAI MATERIAL BIOMEDIS - Ayu Syufiatun Tarigan (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to isolate nanocellulose from oil palm emptry fruit bunches (OPEFB) using acid hydrolysis method. Hydrolysis was carried out for 2 hours using 10% HCl and followed by centrifugation, ultrasonication and dialysis using a semipermeable membrane. The results obtained were tested by FT-IR, and it was found that there was a -OH functional group at a wavenumber between 3000-3500 cm-1, a C-H group in the area 2850-3000 cm-1, -CH2 bending at a wavenumber 1330-1465 cm-1 and the CO group at wave numbers 1000-1100 cm-1. This indicates that the product is in the form of cellulose. The particle size distribution of cellulose was tested with a PSA (Particle Size Analyzer) and the nanocellulose was about 7.2 nm in size.